Portuguese cacholeira blood sausage: A first taste of its microbiota and volatile organic compounds. (October 2020) - Belleggia, Luca; Ferrocino, Ilario; Reale, Anna; Boscaino, Floriana; Di Renzo, Tiziana; Corvaglia, Maria Rita; Cocolin, Luca; Milanović, Vesna; Cardinali, Federica; Garofalo, Cristiana; Clementi, Francesca; Aquilanti, Lucia; et al.
Graphical abstract: Highlights: Microbiota and VOCs of cacholeira blood sausage were investigated. A simple bacterial composition dominated by Lactobacillus sakei was highlighted. Debaryomyces hansenii and Starmerella apicola dominated the fungal population. A seasonal effect on the mycobiota diversity was hypothesized. VOCs included esters, phenols, terpenoids, acids, alcohols, ketones and aldehydes. Abstract: Among typical Portuguese sausages, the cacholeira blood sausage undoubtedly represents one of the most popular preparations. To the authors' knowledge, a lack of information on both the microbiota and the volatile organic compounds (VOCs) of this blood-containing sausage emerges from the available scientific literature. This study represents the first characterization of physico-chemical, microbiological and volatile traits of Portuguese cacholeira blood sausage. To this end, ready-to-eat cacholeira blood sausages were collected from two production batches manufactured in summer (batch 1) and autumn (batch 2). Viable counts showed active microbial communities mainly composed by lactic acid bacteria, coagulase negative cocci, enterococci and eumycetes. The metataxonomic approach showed a simple bacterial composition, which was dominated by Lactobacillus sakei in both the analyzed batches (1 and 2) considered. Carnobacterium, Enterococcus, Kluyvera, Lactococcus and Serratia were found as minor genera. The mycobiota varied according to the production season. Batch 1 was dominated by Starmerella apicola, Debaryomyces hansenii and Candida tropicalis, whereas batch 2 was dominated by D. hansenii . Moreover, Aspergillus spp., Kurtzmaniella zeylanoides, Saccharomyces cerevisiae, Kurtzmaniella santamariae, Brettanomyces bruxellensis and Pichia kluyveri were detected in both the batches as minority species. Seventy-two volatile compounds were identified, including esters, phenols, terpenoids, acids, alcohols, ketones, aldehydes, lactones, furans, sulphur and nitrogen compounds. Significant differences were seen in the amount of some compounds, as a feasible consequence of differences in the raw materials, artisan production and seasonality.